Switched Capacitor Based High Step-Up Multilevel Inverter with Self-Balancing Ability and Low Switching Stress - M. Venkatesan; S. Gouse Basha; A. Ramkumar; R. Manikandan; M. Easwaran; Baseem Khan (International Transactions on Electrical Energy Systems)
In this article, the switched capacitor (SC) based high step-up multilevel inverter is proposed with self-balancing capability. The proposed SC inverter topology is to step up the high output voltage from the very low input voltage without any bulky transformer. This proposed inverter generates single-phase AC voltage with a frequency of 50 Hz from a very low DC input voltage of 50 V with any intermediate DC-DC conversion stage. Hence, the proposed SC inverter is highly suitable for fuel cell, photovoltaic (PV) applications, and shunt active power filter (SAPF). To control the SC inverter, a multicarrier pulse width modulation (PWM) technique is engaged in the inverter. The high step-up voltage level can be achieved by the charging and discharging process of the SC. Furthermore, the stress voltage of the switches does not exceed the applied voltage and the total standing voltage of the inverter is greatly reduced without H-bridges. The comparative analysis of the proposed SC inverter is made for the components, peak inverse voltage (PIV), total standing voltage (TSV), boosting ability, and voltage balancing of capacitors. The main theme of the paper is producing a thirteen-level sinusoidal current with acceptable total harmonic distortion (THD) at different loads, low PIV, TSV, high boosting ability, and self-balancing of capacitors with fewer passive components. The whole system is examined by using MATLAB/Simulink.